الاسْتِيلاَءُ عَلَى التَّرِكَة دِرَاسَةٌ مُقَارِنَةٌ بَيْنَ الفِقْهِ الإسْلاَمِيّ والتَّشْرِيعِ الجَزَائِرِيّ - خولة, حضري; ابتسام, فريحي (جامعة الوادي university of eloued, 2023)
يتعلق موضوع هذه المذكرة بالاستيلاء على التركة والذي سيتم دراسته في الفقه الإسلامي والتشريع الجزائري، فموضوع التركة في حد ذاته موضوع شاسع كونه قابلا للخضوع لمختلف النزاعات مما يحدث بدوره الضغينة والحقد بين أفراد المجتمع، بالرغم من أن الشارع قد فصل في شأنها وكتب لكل ذي حق حقه، إلا أنه يدفع بعض النفوس المريضة إلى التعدي عليها وتسلب الآخرين حقهم منها دون خشية عقاب الله تعالى وقوة القانون؛ لذلك جاءت هذه الدراسة لتعالج هذا الموضوع في فصلين كاملين كل منهما يحتوي على مبحثين، فالفصل الأول جاء عن التركة فقها وقانونا، إذ أوردنا فيه مفهوم التركة وأحكامها في كلا الجانبين، أما الفصل الثاني فتضمن الجزاء المترتب عن هذا الفعل الشنيع في كل من الفقه الإسلامي والتشريع الجزائري، حيث قمنا ببيان معنى مصطلح الاستيلاء عند الفقهاء وكذا ما نص عنه في التشريع الجزائري من خلال عرضنا لمجموعة من المواد القانونية التي توضح ذلك، بالإضافة إلى العقوبة المشروعة التي تدين هذا الجرم في كلا المجالين الفقهي والقانوني، ويهدف هذا البحث إلى بيان وجهة نظر كل من الفقه الإسلامي والتشريع الجزائري لموضوع الاستيلاء على التركة، توعية الناس بمخاطر هذه الظاهرة وآثارها في تفكيك الروابط الأسرية، ومحاولة وضع إضافة نوعية لدعم الدراسات التي عالجت هذا الموضوع، ومن أهم النتائج التي توصلنا إليها على غرار هذا البحث هي موافقة التشريع الجزائري للفقه الإسلامي في أغلب أحكامه على التركة خاصة في قانون الأسرة الجزائري وكذا تجريم كل من الفقه الإسلامي والتشريع الجزائري لفعل الاستيلاء على التركة وقد تبين ذلك من خلال النصوص الفقهية والقانونية بالأخص المادة 363 من قانون العقوبات، كما وضعا عقوبات ردعية للحد من هذه الجريمة (السجن أو الضرب، الضمان) بالنسبة للفقه الإسلامي و(الحبس، الغرامة) في التشريع الجزائري وبالتالي وفرا حماية للتركة من كل محاولة غصب أو الاعتداء عليها تحقيقا للعدل.The graduation thesis concerns the subject of inheritance seizure, which will be studied in Islamic jurisprudence and Algerian law. The subject of the heritage itself is vast because it is submitted to various conflicts, which causes hatred and grudge among members of society, although the legislator has adjudicated it and gave everyone his right, but some sick souls assault and rob others' rights without fear of the punishment of God Almighty or fear of the force of law. It contains the concept of the estate and its provisions on both sides, while the second chapter includes the penalty resulting from this bad act in both Islamic jurisprudence and Algerian law. We have clarified the meaning of the term "seizure" according to jurists as well as what was mentioned about it in Algerian law through our presentation of a set of legal articles that clarify this, in addition to the legitimate punishment that condemns this crime in both the jurisprudential and legal fields. This research aims to clarify the point of view of both Islamic jurisprudence and Algerian law on the subject of the inheritance seizure by educating people about the dangers of this phenomenon and its effects in the dismantling of family ties, and trying to develop a qualitative addition to support studies that dealt with this topic. One of the most important results we have reached in addition to this research is the approval of the Algerian law of Islamic jurisprudence in most of its provisions on the estate, especially in the Algerian family law and also criminalization of both Islamic jurisprudence and Algerian law for the act of inheritance seizure. This has been demonstrated through jurisprudential and legal texts, in particular article 363 of the Penal Code, and they have also established deterrent penalties to curb this crime (imprisonment or beating, guarantee) in relation to Islamic jurisprudence and (imprisonment, fine) in Algerian law, thus providing protection to the estate from any attempt to assault it in order to achieve justice.
شريعة
Keywords: التركة؛ الاستيلاء؛ الفقه الإسلامي؛ التشريع الجزائري.; legacy; seize; Islamic Fiqh; Algerian law.